Is 2030 too soon for Africa to achieve the water and sanitation sustainable development goal? - Nhamo, G.; Nhemachena, Charles; Nhamo, S. (Elsevier, 2019)
Water–Sanitation–Hygiene (WASH) remains vital for the 2030 Agenda for Sustainable Development, yet many countries have not localised the 17 Sustainable Development Goals (SDGs), including SDG 6, which focuses on ensuring the availability and sustainable management of water and sanitation for all. Even in leading African economies such as South Africa, many communities still use the bucket system for sanitation. Using a Composite Index drawn from three indicators whose data were available for 53 of the 54 African countries, it emerged that these states are at various stages of fulfilling the targets set out in SDG 6. The fact that some countries showed declining trends in WASH between 2000 and 2015, is an indication that it will be difficult for Africa to reach the 2030 targets. We recommend that Africa aggressively mobilise resources if it is to attain universal WASH services by 2030, along with other SDG 6-related targets.